2022
DOI: 10.1111/tpj.15843
|View full text |Cite|
|
Sign up to set email alerts
|

The coordination of melatonin and anti‐bacterial activity by EIL5 underlies ethylene‐induced disease resistance in cassava

Abstract: Ethylene and melatonin are widely involved in plant development and environmental stress responses. However, the role of their direct relationship in the immune response and the underlying molecular mechanisms in plants remain elusive. Here, we found that Xanthomonas axonopodis pv. manihotis (Xam) infection increased endogenous ethylene levels, which positively modulated plant disease resistance through activating melatonin accumulation in cassava. In addition, the ethylene-responsive transcription factor ETHY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The Danzhou Mango Germplasm Resource Bank of the Ministry of Agriculture and Rural Affairs provided various tissues and annual seedlings such as roots, young leaves, young stems, flowers, fruits, and seeds, and the variety was “Guifei”. Seedlings were potted in soil (professional growing mix, soil/vermiculite = 2:1) in a greenhouse at 28 °C under a 16/8 h light/dark photoperiod [ 70 , 71 , 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Danzhou Mango Germplasm Resource Bank of the Ministry of Agriculture and Rural Affairs provided various tissues and annual seedlings such as roots, young leaves, young stems, flowers, fruits, and seeds, and the variety was “Guifei”. Seedlings were potted in soil (professional growing mix, soil/vermiculite = 2:1) in a greenhouse at 28 °C under a 16/8 h light/dark photoperiod [ 70 , 71 , 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, infection with Xanthomonas axonopodis pv manihotis ( Xam ) led to an increase in endogenous ET content and the transcription level of ET INSENSITIVE LIKE5 (MeEIL5). MeEIL5 actively modulated disease resistance by interacting with MeHsf20, subsequently promoting the transcriptional activation of the gene encoding N -acetylserotonin O -methyltransferase 2 (MeASMT2) and stimulating melatonin accumulation in cassava . ABA plays a multifaceted role in various plant processes, including stomatal regulation and the initiation of adaptive responses to both biotic and abiotic stressors .…”
Section: Crosstalk Between Et and Other Phytohormones In The Host–pat...mentioning
confidence: 99%
“…MeEIL5 actively modulated disease resistance by interacting with MeHsf20, subsequently promoting the transcriptional activation of the gene encoding N-acetylserotonin O-methyltransferase 2 (MeASMT2) and stimulating melatonin accumulation in cassava. 111 ABA plays a multifaceted role in various plant processes, including stomatal regulation and the initiation of adaptive responses to both biotic and abiotic stressors. 112 Chen and colleagues 113 reported that the WRKY8 TF inhibited tobacco mosaic virus (TMV-cg) infection by regulating ABA and ET pathways, indicating crosstalk between ABA and ET signaling during TMV-cg− Arabidopsis interaction.…”
Section: Phytohormones In the Host−pathogenmentioning
confidence: 99%
“…A recent finding indicated that Xanthomonas axonopodis pv. manihotis ( Xam ) infestation increases levels of intracellular ETH, which modulates disease resistance in plants by inducing the production of MT in cassava roots [ 117 ]. Moreover, the ethylene-responsive transcription factor ETHYLENE INSENSITIVE LIKE 5 (EIL5), known to promote disease resistance, is crucial for the ethylene-induced accumulation of MT in cassava.…”
Section: Mt Eth Ja and Sa: The Cooperation Against Phytopathogensmentioning
confidence: 99%
“…Heat stress transcription factor 20 (Hsf20) physically interacts with EIL5 and led to the activation of the MT biosynthetic gene ASMT2 ( Fig. 6 ), suggesting a link between ETH and MT in plant disease resistance [ 117 ]. Furthermore, increasing of EIL5 protein promotes Hsf20-specific interaction with PR3 , thereby contributing to the anti-bacterial properties of PR3 .…”
Section: Mt Eth Ja and Sa: The Cooperation Against Phytopathogensmentioning
confidence: 99%